Game PAUD Berbasis Matematika (GEMPITA) Guna Meminimalisir Ketakutan Matematika Pada Anak Usia Dini - Anne Mudya Yolanda; Imtikhanah Anis Mahmudiati (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Math seems to be one of the scourges in learning that children are afraid of, even though the use of math is very close and needed in everyday life. This specter or fear is also born from the assumption that the number of calculations and formulas that must be studied is added to the monotonous and rote-only factor of giving material. Therefore, this research was conducted as an effort to improve mathematical logic skills in early childhood thorugh the use of more interesting method in order to be accepted by children. It was the GEMPITA program (a math-based PAUD game). This study uses a literature approach with documentation techniques as a data collection method. In the implementation, the use of various tools and technology is able to increase children the attractiveness to learning mathematical concepts. So that the results are in the form of recommendations for math-based games that are easy and fun to minimize math fear in early childhood.